Short-Term Results of One Day Surgery at the Digestive Surgery Department of Yaounde Central Hospital - CHOPKENG NGOUMFE, Joseph Cyrille; BWELLE MOTTO, Georges; EKANI BOUKAR, Yannick Mahamat; BANG, Guy Aristide; TIM TIENTCHEU, Fabrice; ESSOMBA, Arthur (British Journal of Healthcare and Medical Research, 2023)
Introduction: Ambulatory surgery, though widespread in the world remains in an embryogenic phase in Africa. The aim of this study was to evaluate the prognosis of ambulatory patients (out patients) in our context. Method: We conducted a descriptive cross-sectional study over an 11-month period at the Yaoundé Central Hospital. The parameters studied were clinical and social according to the criteria of the Ouagadougou Quality Life index (OQLI). Results: We included 33 patients (21 men and 12 women) with a sex ratio of 1.75 M/F and a mean age of 38.45 years with extremes ranging from 21 to 74 years. Proctologic disorders accounted for 63.7% followed by wall disorders in 21.3% of cases. Patients were classified ASAI (81.80%), ASAII (15.20%) and ASAIII (3%). Spinal anesthesia was used in 78.8% of cases. The mean duration of intervention was 21.89 minutes with a pain intensity at 24h postoperative between 4 and 6 according to the Visual Analog Scale. 78.8% of patients had a hospital stay equal to 24 hours and 21.2% less than 24 hours. Complications were headache and postoperative nausea and vomiting with a morbidity of 0.18%. There were no cases of infection and no mortality. The criteria of the Ouagadougou Quality Life Index were improved and appreciable in short term. Conclusion: Ambulatory surgery would improve the level of care for a significant category of patients in various specialties.